Repair and Reconstruction of Telomeric and Subtelomeric Regions and Genesis of New Telomeres: Implications for Chromosome Evolution. (1st April 2020) - Kim, Chuna; Sung, Sanghyun; Kim, Jun; Lee, Junho
Abstract: DNA damage repair within telomeres are suppressed to maintain the integrity of linear chromosomes, but the accidental activation of repairs can lead to genome instability. This review develops the concept that mechanisms to repair DNA damage in telomeres contribute to genetic variability and karyotype evolution, rather than catastrophe. Spontaneous breaks in telomeres can be repaired by telomerase, but in some cases DNA repair pathways are activated, and can cause chromosomal rearrangements or fusions. The resultant changes can also affect subtelomeric regions that are adjacent to telomeres. Subtelomeres are actively involved in such chromosomal changes, and are therefore the most variable regions in the genome. The case of Caenorhabditis elegans in the context of changes of subtelomeric structures revealed by long‐read sequencing is also discussed. Theoretical and methodological issues covered in this review will help to explore the mechanism of chromosome evolution by reconstruction of chromosomal ends in nature. Abstract : Telomeres are protective structures for linear chromosomes, which are usually maintained by an enzyme called telomerase. In nature, telomeres are often severely worn out by spontaneous DNA damage, and telomerase‐independent repair mechanisms can be initiated. Resulting rearrangements or fusions near telomeres make new chromosomal structures and thus contribute to chromosome evolution.